Evaluation of damage indexes for structural health monitoring in nonlinear mechanical systems based on Volterra series - Shiki, Sidney Bruce [UNESP]; Da Silva, Samuel [UNESP] (IOP Publishing, 2015)
Nonlinear behavior can be important for the monitoring of the structural state of mechanical systems since it can be mistakenly classified as a damage in the systems. However, nonlinear tools are still not consolidated and need further research for applications in mechanical system. Discrete-time Volterra series is an interesting mathematical framework to deal with nonlinear dynamics. It is a clear generalization of the linear convolution for weakly nonlinear systems. In the present work two different damage indicators are proposed based on Volterra models by considering linear and nonlinear contributions of the total response. The goal is to evaluate these indicators using an experimental test rig where the damages are simulated and considering the nonlinear regime of motion. The main advantages and drawbacks of the proposed methodology are highlighted in the final remarks.